ANALYSIS OF SUBSIDIES IN CROATIAN BEEKEEPING - Z. Puškadija (Poljoprivreda, 2001)
Beekeeping in Croatia unlike many other productions was not subsidized until mid nineties. At the time of introduction of first subsidies honey market was very inefficient, and there was hardly any market for other bee products. Several years of implementation enables first analyses. The investigation is based on two complementary data sets, quantitative data on production and subsidies and farmers attitude toward importance of various measures. Croatian beekeepers compared with their colleagues from other transitional countries make business quite well. Major characteristics of Croatian beekeeping are low density (2.7 beehives per km2), relatively high degree of concentration (22.7 beehives per beekeeper) and relatively intensive production (20 kg of honey per beehive and year). Additional importance to the beekeeping gives the export being more than 1/10 of honey production. Introduction of subsidy for honey production in 1998 resulted in 12% increased annual production in 1999. Besides, a number of beehives increased by 11% in 1999, after just one year of beekeeping subsidy. According to HSSC-a in 1997 Croatian beekeepers produced 16000 queens. In 2001 they produced already 38968. Investigation of farmers’ attitude toward influence of various subsidies on their business decisions showed that more than half of beekeepers claimed they were not influenced at all. Subsidies for honey production and queen production had, partially or fully influence on decisions of 25% beekeepers. Subsidy for queen testing had partially or fully influence on decisions of 25% beekeepers. Subsidy for beekeeping was the most important for beekeepers (30.8% of beekeepers were partially or fully influenced), although implementation of this measure was difficult since there is no registry of the beekeepers.